Performance of Hydrated Cement Treated Crushed Rock Base as a Road Base Material in Western Australia - Chummuneerat, Suphat; Jitsangiam, Peerapong; Nikraz, Hamid (The Australian Geomechanical Society and New Zealand Geotechnical Society, 2012)
Hydrated Cement Treated Crushed Rock Base (HCTCRB) is produced by adding 2%-Portland cement with standard crushed rock base. The mixture is disturbed after the specific hydration period to prevent setting up and retain its unbound property. HCTCRB has been commonly adopted for Western Australian roads, however based on empirical method and experiences. Thus, the characterisation of HCTCRB following the pavement mechanistic approach is needed. This paper aims to presents the performances of HCTCRB in terms of permanent deformation and resilient modulus. The repeated load triaxial tests were performed to study the performances of HCTCRB that affected by manufacturing (hydration period) and construction procedures (amount of water added during compaction and dry back). This study has found that HCTCRB exhibited the stress dependent behaviour. All these studied factors significantly affect the resilient performances of HCTCRB in dissimilar trends. The certain impact on the material performances related to the hydration periods still could not be concluded. The higher water addition even at the optimum moisture content of HCTCRB resulted in the poorer performances, although it induced the higher dry density, which indicated that the HCTCRB is still susceptibility to moisture content. The dryback process has potential to improve the material performances of the material in different level which depends on amount of additional water. All the tested results indicated the significant influence of moisture content to the performances of HCTCRB with regardless of the dry density.